The corrected QT (QTc) prolongation in hyperthyroidism and the association of thyroid hormone with the QTc interval - Ye Seung Lee; Joong Wan Choi; Eun Ju Bae; Won Il Park; Hong Jin Lee; Phil Soo Oh (Korean Pediatric Society, 2015)
PurposeVentricular repolarization is assessed using the QT interval corrected by the heart rate (QTc) via an electrocardiogram (ECG). Prolonged QTc is associated with an increased risk of arrhythmias and cardiac mortality. As there have been few reports regarding the effects of hyperthyroidism on ventricular repolarization, we studied the association between serum free thyroxine (free T4 [fT4]) and thyroid stimulating hormone (TSH) levels and the QTc interval.MethodsThirty-eight patients with hyperthyroidism (<30 years old) were included, and we used their clinical records and available ECGs (between August 2003 and August 2011) to evaluate the association between their fT4 and TSH levels and their QTc interval. In addition, we studied the ECGs of 72 age-matched patients with no hyperthyroidism (control group) and compared their data with that from the patients group.ResultsThe QTc duration in patients with hyperthyroidism was significantly prolonged compared to that in the control subjects (P<0.001). In addition, the number of hyperthyroid patients with abnormal prolonged QTc was significantly higher than that in the control group (P<0.001). Among the patients with hyperthyroidism, patients with prolonged QTc and borderline QTc had higher fT4 levels and there was positive correlation between their fT4 levels and their QTc interval (P<0.05). However, no correlation was observed between their TSH levels and their QTc interval.ConclusionWe report that hyperthyroidism is associated with QTc prolongation. The correlation between the fT4 levels and the QTc interval suggests that thyroid status is associated with QTc values and the risk of cardiac mortality.